Analisis Determinan Produktivitas Tenaga Kerja di Indonesia tahun 2015-2020 - Ivan Masduqi Mahfuds; Rita Yuliana (Seminar Nasional Official Statistics, 2022)
National development is an effort to improve all aspects of people's lives with the aim of realizing people's welfare. The current labor problem in Indonesia is the low labor productivity. growth in labor productivity that is not in line with constant increases is indicated by the minimum wage which has increased over the last five years, growth tends to decline. This study aims to analyze the general picture of labor productivity in Indonesia in 2015-2020, as well as analyze the variables that affect labor productivity in Indonesia in 2015-2020. The analytical methods used in this research are thematic maps, scatter diagrams, and inferential analysis using panel data regression. The best model chosen is the Fixed Effects Model Seemingly Unrelated Regression. The results showed that the provincial minimum wage and real expenditure per capita had a positive effect, while life expectancy had a negative effect on labor productivity